Glycogen in the uterus and fallopian tubes is an important source of glucose during early pregnancy. Issue 2 (14th June 2019) - Dean, Matthew
Abstract: Pregnancy loss is common during the peri-implantation period in mammals when glucose is required for both embryonic development and decidualization of the endometrium. As the uterus cannot synthesize glucose, all glucose must come directly from maternal circulation as needed or transiently stored as the macromolecule glycogen. Glycogen acts as a glucose reservoir, storing up to 55 000 glucose moieties per molecule. Endometrial glycogen concentrations are correlated with fertility in humans, indicating that glycogen is an essential source of glucose during early pregnancy. In humans and primates, endometrial glycogen concentrations peak during the luteal phase due to progesterone. In contrast, in rats and mink, estradiol triggers an accumulation of uterine glycogen during proestrus and estrus. In mated rats, the glycogen content of the endometrium increases again after implantation due to high levels of glycogen stored in the decidua. In mink, endometrial glycogen reserves are localized in the uterine epithelia at estrus. These reserves are mobilized before implantation, suggesting they are used to support embryonic growth. Uterine glycogen concentrations continue to decrease after implantation in mink, probably due to a lack of decidualization. How ovarian steroids stimulate glycogenesis in the endometrium is unclear, but current evidence suggests that estradiol/progesterone interacts with insulin or insulin-like growth factor signaling. In summary, endometrial glycogen is an essential source of glucose during the peri-implantation period. More work is needed to characterize differences among species, elucidate the fate of the glucose liberated from glycogen, and understand how ovarian steroids regulate glycogen metabolism in the uterus. Abstract : Glycogen in the uterus and oviducts represents an important source of glucose to support the uterus and embryos early pregnancy.